A fast responsive, highly selective and light-up fluorescent probe for the two-photon imaging of carboxylesterase in living cells. Issue 11 (1st March 2018) - Wang, Jianguo; Chen, Qingqing; Tian, Na; Zhu, Wenping; Zou, Hang; Wang, Xuesong; Li, Xiaokang; Fan, Xiaolin; Jiang, Guoyu; Tang, Ben Zhong
Abstract : A fast responsive and two photon fluorescent probe (HCyNAc) for carboxylesterase (CaE) has been designed and used for the two-photon imaging of the endogenous CaE level in living HeLa cells under 800 nm NIR excitation. Abstract : A fast responsive and two photon fluorescent probe (HCyNAc) for carboxylesterase (CaE) has been designed based on the D–π–A structure of hemicyanine and naphthalene derivatives. After enzymatic reaction, HCyNAc enabled light-up fluorescence assay of CaE over other biologically-relevant species and enzymes, including ROS. Two-photon imaging of endogenous CaE was confirmed in HeLa cells using HCyNAc under 800 nm NIR excitation.